PROBLEMS OF FORMATION OF IMAGE AND SOCIAL RESPONSIBILITY OF STATE FISCAL SERVICE BODIES IN UKRAINE - Revenko O.V. (Pressing Problems of Public Administration, 2018)
The problems and characteristics of image formation of the fiscal organization. The directions of development of social responsibility of State Fiscal Service bodies based on the strategic principles.